Grease on: perspectives in lipid droplet biology - Beller, Mathias; Herker, Eva; Füllekrug, Joachim (Seminars in cell & developmental biology, 2020)
Lipid droplets (LDs) are now recognized as omnipresent and dynamic subcellular organelles of amazing morphological and functional diversity. Beyond the obvious benefit of having molecules full of chemical energy stored in a dedicated structural entity, LDs may also be viewed as a safe harbor for potentially damaging metabolites. This protective function might in many cases even supersede the relevance of lipid storage for eventual energy gain and membrane biogenesis. Furthermore, the LD surface constitutes a unique membrane environment, creating a platform for hosting specific proteins and thus enabling their interactions. These metabolic hotspots would contribute decisively to compartmentalized metabolism in the cytosol. LDs are also communicating extensively with other subcellular organelles in directing and regulating lipid metabolism. Deciphering the relevance of LD storage and regulation at the organismic level will be essential for the understanding of widespread and serious metabolic complications in humans. Increasing attention is also devoted to pathogens appropriating LDs for their own benefit. LD biology is still considered an emerging research area in rapid and vibrant development, attracting scientists from all disciplines of the life sciences and beyond, which is mirrored by the accompanying review collection. Here, we present our personal views on areas we believe are especially exciting and hold great potential for future developments. Particularly, we address issues relating to LD biogenesis and heterogeneity, required technological advances, and the complexity of human physiology.